DETERMINAN STRATEGIC PARTNER SUMBER DAYA MANUSIA PADA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA MAGELANG - Kesi Risnawati; lukluk atul Hidayati (Universitas Ahmad Dahlan, 2014)
This research aims to analyze whether the infl uence of knowledge management, strategic planning and organizational culture on strategic HR partner in Tax offi cer Pratama Magelang either simultaneously or partially. The method used was purposive sampling, with 50 respondents. The analytical tool used is multiple linier regression. The result shows that there is a signifi cant effect simultaneously or jointly of knowledge management, strategic planning, and organizational culture on strategic partner. The effect of 59.9% while the remaining 40,1% is infl uenced by other variables that they are not examined. Strategic planning is a variable that has the most dominant infl uence on HR strategic partner.